The old, unique C1 chondrite Flensburg: insight into the first processes of aqueous alteration, brecciation, and the diversity of water-bearing parent bodies and lithologies - Bischoff, Addi; Alexander, Conel M. O'D.; Barrat, Jean-Alix; Burkhardt, Christoph; Busemann, Henner; Degering, Detlev; Di Rocco, Tommaso; Fischer, Meike; Fockenberg, Thomas; Foustoukos, Dionysis I.; Gattacceca, Jérôme; Godinho, Jose R. A.; et al. (Geochimica et cosmochimica acta, 2021)
On September 12, 2019 at 12:49:48 (UT) a bolide was observed by hundreds of eye-witnesses from the Netherlands, Germany, Belgium, Denmark and the UK. One day later a small meteorite stone was found by accident in Flensburg. The presence of short-lived cosmogenic radionuclides with half-lives as short as 16days proves the recent exposure of the found object to cosmic rays in space linking it clearly to the bolide event. An exceptionally short exposure time of ∼5000years was determined. The 24.5g stone has a fresh black fusion crust, a low density of <2g/cm3, and a magnetic susceptibility of logχ=4.35 (χ in 10−9 m3/kg). The rock consists of relict chondrules and clusters of sulfide and magnetite grains set in a fine-grained matrix. The most abundant phases are phyllosilicates. Carbonates (∼3.9 vol.%) occur as calcites, dolomites, and a Na-rich phase. The relict chondrules (often surrounded by sulfide laths) are free of anhydrous silicates and contain abundant serpentine. Lithic clasts are also surrounded by similar sulfide laths partly intergrown with carbonates. 53Mn-53Cr ages of carbonates in Flensburg indicate that brecciation and contemporaneous formation of the pyrrhotite-carbonate intergrowths by hydrothermal activities occurred no later than 4564.6±1.0Ma (using the angrite D'Orbigny as the Mn-Cr age anchor). This corresponds to 2.6±1.0 or 3.4±1.0Ma after formation of CAIs, depending on the exact absolute age of CAIs. This is the oldest dated evidence for brecciation and carbonate formation, which likely occurred during parent body growth and incipient heating due to decay of 26Al. In the three oxygen isotope diagram, Flensburg plots at the 16O-rich end of the CM chondrite field and in the transition field to CV-CK-CR chondrites. The mass-dependent Te isotopic composition of Flensburg is slightly different from mean CM chondrites and is most similar to those of the ungrouped C2 chondrite Tagish Lake. On the other hand, 50Ti and 54Cr isotope anomalies indicate that Flensburg is similar to CM chondrites, as do the ∼10 wt.% H2O of the bulk material. Yet, the bulk Zn, Cu, and Pb concentrations are about 30% lower than those of mean CM chondrites. The He, Ne, and Ar isotopes of Flensburg show no solar wind contribution; its trapped noble gas signature is similar to that of CMs with a slightly lower concentration of 20Netr. Based on the bulk H, C, and N elemental abundances and isotopic compositions, Flensburg is unique among chondrites, because it has the lightest bulk H and N isotopic compositions of any type 1 or 2 chondrite investigated so far. Moreover, the number of soluble organic compounds in Flensburg is even lower than that of the brecciated CI chondrite Orgueil. The extraordinary significance of Flensburg is evident from the observation that it represents the oldest chondrite sample in which the contemporaneous episodes of aqueous alteration and brecciation have been preserved. The characterization of a large variety of carbonaceous chondrites with different alteration histories is important for interpreting returned samples from the OSIRIS-REx and Hayabusa 2 missions.
Available online 24 October 2020
Gesehen am 03.02.2021